Analisis Pengaruh Zakat, Pembiayaan Syariah, Tingkat IPM (Indeks Pembangunan Manusia) dan APBA (Anggaran Pendapatan Belanja Aceh) Terhadap Pengentasan Kemiskinan di Aceh - Surya Alfi Nurrahma; Tri Inda Fadhila Rahma; Khairina Tambunan (Journal of Islamic Economics and Finance, 2024)
This research aims to analyze the influence of Zakat, Sharia Financing, Human Development Index (HDI) Level, and Aceh Revenue and Expenditure Budget (APBA) on Poverty Alleviation in Aceh. This research uses a descriptive quantitative approach and explanatory panel data for 10 years. This research uses secondary data obtained from world data banks, journals, books and other supporting references. The analytical tool used in this research is SPSS 22 with multiple regression analysis techniques. The research results show that the partial significant test of the Zakat variable is obtained from the results of the t test where the calculated t value is 0.338 < t table 1.692, so it can be concluded that zakat has no effect on poverty alleviation in Aceh. Meanwhile, the Sharia Financing variable is obtained from the results of the t test where the t value is 1.834> t table 1.692, so it can be concluded that sharia financing has an effect on poverty alleviation in Aceh. Meanwhile, the variable level of the Human Development Index (HDI) can be seen from the results of the t test where the t value is 1.872> t table 1.692, so this shows that the sharia development index has an effect on poverty alleviation in Aceh. Meanwhile, the Aceh Revenue and Expenditure Budget (APBA) variable can be seen from the results of the t test where the value of tcount is 1.236 < t table 1.692, it is concluded that the Aceh Revenue and Expenditure Budget (APBA) has no and significant influence on poverty alleviation in Aceh. Meanwhile, together (simultaneously) the variables zakat, sharia financing, human development index level and the Aceh income and expenditure budget have an effect on poverty alleviation. It can be seen that the calculated F value is 13.466 with a sig value of 0.000<0.05, where the calculated F value is 13.466>2.66.